HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN KONSUMEN DI RUMAH MAKAN LAMUN OMBAK PADANG - Witrin, Rosy; Chair, Ira Meirina; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This study aims to: 1) Describe the quality of service in Restaurant Lamun Ombak Padang, 2) Describe the consumer satisfaction in Restaurant Lamun Ombak Padang, and 3) Analyzing there a relationship between service quality and customer satisfaction in Restaurant Lamun Ombak Padang. This type of research is classified to correlational studies. The population in this study are all consumers Restaurant Lamun Ombak Padang totaling 9050 people. The study sample totaled 100 people with the sampling technique was non probability sampling, by using incidental sampling. Data was collected using a questionnaire (questionnaire) by using a Likert scale that has been tested for validity and reliability. The study found that: 1) Quality of Service in the category fairly (50%), with as many details as (2%) showed excellent category, (44%) showed either category, (50%) showed enough categories, (4%) showed poor category and none (0%) which showed poor results at all 2) is in the category Consumer Satisfaction enough (72%), with details (1%) showed excellent category, (27%) showed either category, (72%) showed enough categories, none (0%) showed poor category, and none (0%) showed poor results at all.